Effect of cDMEM media containing Ectoine on human periodontal ligament mesenchymal stem cell survival and differentiation - (:unkn) unknown (WILEY, 2018)
Background/AimEctoine is an amino acid that can preserve osmotic balance and has more preservative activity than other osmoregulators. There are no published reports on the osmoregulators' effects on viability or differentiation of dental stem cells. The aim of this study was to investigate the effect of Ectoine as a storage media on the viability and differentiation potential of human periodontal ligament mesenchymal stem cells (hPDLMSCs). Materials and MethodshPDLMSCs were obtained from impacted third molar teeth. The cells were isolated, submitted to trilineage differentiation, and characterized by flow cytometer (FC). hPDLMSCs were incubated with different media containing Ectoine, complete DMEM (cDMEM), Ectoine+cDMEM, milk, and tap water for 2, 6, 12, and 24h. The cells were analyzed by FC for viability, early-apoptosis, late apoptosis, and necrosis rates. Osteogenic and fibroblastic differentiation in hPDLMSCs were investigated by Alizarin red stain and vimentin expression. ResultsAll treated groups showed significant decreases in cell viability after 2h. Significant increases were detected in the number of dead cells between 2 and 12h in all groups except the Ectoine+cDMEM group. The deposition of mineral matrix nodules was significantly higher in cells cultured with Ectoine+cDMEM compared with the other media. Higher vimentin expressions were detected in cells cultured with cDMEM and Ectoine+cDMEM media, respectively. ConclusionsEctoine added to cDMEM media, promoted cell survival plus osteogenic and fibroblastic differentiation of hPDLMSCs.
Keywords: cell viability; ectoine; fibroblastic differentiation; osteogenic differentiation; periodontal ligament cells; TRAUMATIC DENTAL INJURIES; STORAGE MEDIA; IN-VITRO; AVULSED TEETH; GROWTH-FACTORS; STROMAL CELLS; COCONUT WATER; VIABILITY; MILK; PLASTICITY